EFFECTS OF GAMES ON DEVELOPMENT OF 3-5 AGES OF CHILDREN ON PREPCHOOL CHILDREN - Selda KATLAV (Fırat University, 2019)
Games play a crucial role on the development of education and personality. Childeren unconsciously gains several personal and physical abilties in games. The aim of this study is to define thoughts of prepschool teachers on the the effects of games on development of 3-5 years old of childeren on prepschool childeren. There are several studies related to improvement of pre-school children. However, there is lack of literature about games which are teaching from their teachers. According to author knowledge, there is no paper especially for Northern Cyprus. With this study, it is aim to fill this absence in the literature with chosen pilot area and this will give important information to other countries. Although this study selected schools all the NC within the borders of the current state of one to one it does not reflect the study to be conducted of the game with 3-5 years preschool effects on children and teachers be consulted later studies sources and retention issues tend to be shown in terms of importance. In the same manner Cyprus issue in perspective of teachers with knowledge of the child, the relationship between the effects of the game and the importance of teachers will be exposed. It is provided importance with the data obtained in this study and observations to be carried on further aspects of community education and with unwidely studies and the findings from opinions and experience of teachers will be provided to improve new methods and applications for more effective education. Additionally, with this study, it is targeted how much importance teachers give to games in their annual plans in Nourthern Cyprius, which criterias teachers choose games and meterials in game period, which issues teachers give importance at game time, deviation of game and reasons to choose them, dete mination of games, identification of difficulties of children when they play games, children participate in the game process followed in determining ways to motivate teachers of the game effects on children.